Host Habitat as a Dominant Role in Shaping the Gut Microbiota of Wild Crucian Carp (Carassius auratus) - Xinghao Li; Xueli Huang; Liya Zhao; Wei Cai; Yuhe Yu; Jin Zhang (Fishes, 2023)
Current knowledge on the fish gut microbiota has largely been obtained from experiments on laboratory-reared animals. Here, the crucian carp (Carassius auratus) with a mean weight of 159.9 ± 11.4 g (mean ± SD) were collected from their natural habitats (i.e., Wuhu lake and Poyang lake, China), and the gut microbiota were analysed by using the next-generation sequencing of 16S rRNA gene. We obtained more than 430,000 high-quality reads, which constituted more than 1200 operational taxonomy units (OTUs), revealing extremely diverse microbes in the fish gut. Proteobacteria, Fusobacteria, Bacteroidetes and Firmicutes were detected as the prominent phyla (each > 1% of total abundance) within the gut microbiota, regardless of the host habitat or the gut segment (i.e., foregut vs. hindgut). Although the microbes in the hindgut were more diverse (OTU number, Shannon and Chao1; One-way Anova, p > 0.05) than in the foregut, the host habitat had a significant role in shaping the community structures (MRPP, ANOSIM, PERMANOVA, p < 0.01). Interestingly, we also detected a set of common OTUs, whereby genera Aeromonas and Cetobacterium might comprise the core gut microbiota of crucian carp.